The Concept of Minority in Urdu Novels - Nawaz, Huma; Haider, Safeer (sourcecoder, 2022)
In this article, research has been shed on the concept of minorities in Urdu novels and a successful attempt has been made to see what was the concept of minorities in the novels written in the neo-colonial period before the establishment of Pakistan and Pakistanis written after the establishment of Pakistan. How the concept of minorities in Urdu novels has changed at national and international level. Thus, the concept of minorities seems to be evolving. All these concepts have been certified with the help of the characters and texts of Urdu novels. And by bringing the exploitation and rights of minorities to the fore, attention has been drawn towards human equality.